Impact of irrigation, nitrogen fertilization, and plant density on stay-green and its effects on agronomic traits in maize - Chibane, Nadia; Revilla, Pedro; Yannam, Venkata Rami Reddy; Marcet, Purificación; Covelo, Emma Fernández; Ordás, Bernardo (Frontiers in Plant Science, 2024)
The stay-green (SG) or delayed leaf senescence enables crop plants to maintain their green leaves and photosynthetic capacity for a longer time after flowering. It is considered an important trait in maize breeding which has contributed to gain in grain yield of modern varieties. It has been also used to improve the tolerance to drought and deficiencies in nitrogen fertilization. However, the objectives of this study were to evaluate the influence of water irrigation (WI), nitrogen fertilization (NF) and plant density (PD) on SG and on the effect of SG on agronomic traits in maize. Four SG lines and four no stay green (NSG) lines were evaluated in four contrasting environments under two WI, three NF and two PD levels. As expected, the chlorophyll content of leaves at 45 days after flowering (Chlo45) was on average higher in the SG group of lines. The difference in Chlo45 between the SG and NSG genotypes was consistent across WI, NF and PD, and environments. This is indicative that internal or developmental factors were more important that external signals in controlling the senescence. The effect of SG increasing thousand-kernel weight (TKW), stover yield at harvest or moisture were not influenced by WI, NF or PD, but was altered by the background environment. Our results have implications for the application of SG as a secondary trait for enhancing abiotic stress tolerance. Future studies could consider a wider range of environmental conditions to assess the performance of SG traits under different climatic and soil conditions.